Effects of Semantic Neighbourhood Density on Spoken Word Production - Hameau, Solène; Biedermann, Britta-Andrea; Nickels, Lyndsey (2019)
When producing words, it is generally agreed that semantically related words are activated along with the target. However, relatively little is known about the extent to which the number of such semantically related words affects the production of spoken words. The research presented here explores, in detail, the influence of semantic neighbourhood density – the number of words of similar meaning in the lexicon - on picture naming performance in both unimpaired speakers and a large group of individuals with aphasia. In Experiment 1, six different semantic neighbourhood density measures were compared using principal component analysis. Four different semantic neighbourhood density components were identified: feature-based, context-based, association-based and distant. In Experiment 2, these new measures were used as predictors in analysis of picture naming data from unimpaired English speakers: no significant effects of semantic neighbourhood factors were observed on either latency or accuracy. Finally, Experiment 3 reports an analysis of picture naming responses of a large group of individuals with aphasia (n=193), examining the influence of the semantic neighbourhood density measures. Effects of the feature-based semantic neighbourhood measure on accuracy varied across participants with no overall main effect. This same measure increased the probability of a coordinate error compared to a correct response but also compared to an omission. Results are best accommodated by theories of word production that incorporate mechanisms by which semantically related concepts can both facilitate and inhibit target production.